2022
DOI: 10.1155/2022/5628687
|View full text |Cite|
|
Sign up to set email alerts
|

The Clinical Application of Remimazolam Benzenesulfonate Combined with Esketamine Intravenous Anesthesia in Endoscopic Retrograde Cholangiopancreatography

Abstract: In this project, algorithm-based image processing methods in 3D endoscopic image processing endoscopic retrograde cholangiopancreatography (ERCP) were analyzed. To enhance local information of images, an adaptive histogram equalization method with limited contrast is introduced. The influences of the algorithm on 3D endoscopic image peak signal-to-noise ratio (PSNR), image discrete information entropy (DE), and average mean brightness error (AMBE) of images before and after the optimization before were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Studies have shown that esketamine combined with propofol or remimazolam for procedural sedation can maintain stable hemodynamics and reduce the incidence of adverse events ( Chen et al, 2022 ; Xu et al, 2022 ; Yi et al, 2022 ; Zhan et al, 2022 ; Zheng et al, 2022 ). Zhao et al reported that 84.8% of injection pain occurred in pediatric patients with propofol, which could be reduced by ketamine pretreatment ( Zhao et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that esketamine combined with propofol or remimazolam for procedural sedation can maintain stable hemodynamics and reduce the incidence of adverse events ( Chen et al, 2022 ; Xu et al, 2022 ; Yi et al, 2022 ; Zhan et al, 2022 ; Zheng et al, 2022 ). Zhao et al reported that 84.8% of injection pain occurred in pediatric patients with propofol, which could be reduced by ketamine pretreatment ( Zhao et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is consistent with a study on S‐ketamine in treating vascular response to depression. Intravenous injection of S‐ketamine (0.5 mg/kg) reduced HR and blood pressure fluctuations, thus stabilizing hemodynamics 31 . This is because hemodynamic disorders in clinical anesthesia often manifest as negative changes caused by inhibition of the sympathetic system, but the sympathomimetic effect of S‐ketamine counteracts this unfavorable fluctuation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous trials have consistently demonstrated that remimazolam has a better safety profile than propofol, including less bradycardia treatment requirement, a lower incidence of hypotension, and less injection pain 18,19,34,35,39,40,43,44,46 . However, propofol was less likely to develop postoperative nausea and vomiting (PONV) 19,46 .…”
Section: Discussionmentioning
confidence: 99%
“…28,33 Due to its analgesic properties, esketamine can potentially alleviate pain experienced by patients during surgical abortion, minimizing pain-induced body movements, and fluctuations in hemodynamics during the procedure. Remimazolam coadministrated with esketamine (R + E) could provide both effective sedation and analgesia for routine outpatient procedures, which could be an alternative to the increasingly used P + E. The combination use of R + E has been shown to have better profiles over propofol co-administered with sufentanil 34 and fentanyl 35 for procedures like gastroscopy co-administrated with other analgesics. Esketamine is increasingly used in combination with propofol (P + E), to reduce propofol consumption and propofolinduced injection pain.…”
Section: Introductionmentioning
confidence: 99%